verBERT: Automating Brazilian Case Law Document Multi-label Categorization Using BERT - Serras, Felipe R.; Finger, Marcelo (Anais do Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana (STIL); 2021: Anais do XIII Simpósio Brasileiro de Tecnologia da Informação e da Linguagem HumanaDO - 10.5753/stil.2021.17803, 2021)
In this work, we carried out a study about the use of attention-based algorithms to automate the categorization of Brazilian case law documents. We used data from the Kollemata Project to produce two distinct datasets with adequate class systems. Then, we implemented a multi-class and multi-label version of BERT and fine-tuned different BERT models with the produced datasets. We evaluated several metrics, adopting the micro-averaged F1-Score as our main metric for which we obtained a performance value of 〈F 1 〉 micro = 0.72 corresponding to gains of 30 percent points over the tested statistical baseline.